Potential drug-drug interactions on in-patient medication prescriptions at Mbarara Regional Referral Hospital (MRRH) in western Uganda: prevalence, clinical importance and associated factors - SJ, Lubinga; E, Uwiduhaye (African Health Sciences, 2011)
Background: Drug-drug interactions (DDIs) are an important cause of adverse drug reactions. The pharmacoepidemiology of such interactions in hospitals in Uganda is not known. Objectives: To determine the prevalence, clinical importance and factors associated with potential DDIs at Mbarara Regional Referral Hospital (MRRH), western Uganda. Methods: Retrospective analysis of 235 randomly selected hospitalization episodes (medication charts and medical notes) from MRRH over a 1-year period from January to December 2008. We collected data on demographics, medications, principal diagnosis, co-morbid conditions and the length of hospital stay. Epocrates Rx® was used to identify and classify potential DDIs according to mechanism and management strategy. Descriptive statistics were generated and logistic regression used to determine associated factors. Results: Overall prevalence of potential DDIs was approximately 23% (54 medication charts with at least one potential DDI out of 235 hospitalization episodes). Majority were postulated to occur through a pharmacodynamic mechanism (10.6%) and most required either “use with caution” (11.9%) or “modify treatment/monitor” (10.6%) as a suggested management strategy. After adjusting for confounders: age, sex, hospital department and number of co-morbid conditions, a principal diagnosis of a cardiovascular disease (OR 6.52 95% CI 1.32-32.14) and having 4 or more medicines on the chart (OR 4.30 95% CI 1.98-9.34) were associated with the presence of a potential DDI. Conclusion: Potential DDIs frequently occur at MRRH although most are not clinically significant. Patients with cardiovascular diseases and those who are prescribed multiple medications need to be monitored more closely
Keywords: Drug-drug interactions; Pharmacoepidemiology; Prevalence; Chart review